Association of Ischaemic Heart Disease with Hospitalized Ischaemic Stroke Patients in a Tertiary Care Hospital - Kabir, Nazmul; Ahmed, KM Ahsan; Sarker, Md Sadekur Rahman; Chowdhury, Md Tauhidul Islam (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Stroke and IHD is a major health problem all over the world. But few studies have been done in our country to see the association of IHD among ischaemic stroke patients. Objective: The purpose of the present study was to evaluate the prevalence of IHD among hospitalized ischaemic stroke patients and to identify their common risk factors. Methodology: This was a cross-sectional study carried out in 50 ischaemic stroke patients admitted in Medicine Wards of Khulna Medical College Hospital, from July 2012 to December 2012. The patients were taken in both sexes having more than 18 years age and CT-scan evidence of ischaemic stroke by purposive sampling technique. After recruitment of patients IHD was established by ECG findings. Subsequently other risk factors were identified and were recorded. Results: The incidence of stroke for individuals older than 80 years was approximately 30.0% compared with 8.0% for individuals between 31 to 40 years of age. Among them IHD was more common in 51 to 60 years old stroke patients (33.33%) but less common in older than 80 years of age (8.33%). All of those having both ischaemic stroke and IHD were hypertensive. Among them 58.33% cases had severe hypertension but those having only stroke but no IHD 73.68% cases were hypertensive. Among them 34.21% had severe hypertension. Regarding lipid profile those having both ischaemic stroke and IHD 83.33% were dyslipidaemic but of those having only stroke but no IHD 52.63% were dyslipidaemic. This study revealed 41.67% diabetic patients developed both Ischaemic stroke and IHD compared to 31.58% diabetic patients developed only ischaemic stroke. Conclusion: In conclusion IHD and ischaemic stroke patients share similar pathophysiological mechanisms and, consequently, many risk factors. Journal of National Institute of Neurosciences Bangladesh, July 2023; 9(2):98-102